(untitled) (REMUNOM, 2024)
The search for the inclusion of biodiesel in the energy matrix has been one of the objectives of several countries and trade blocs. In Brazil, numerous studies have been conducted with different oilseeds for biodiesel production. In the Amazon, one of the oil seeds with potential for biodiesel production is the jatropha. The jatropha, Jatropha Curcas L., is a species native to tropical America, resistant to pests and diseases, and adaptable to highly variable environmental conditions (soil and climate). In this context, given the favorable characteristics and natural availability of jatropha in the Amazon region, especially on properties near Itacoatiara, this study proposed studies to optimize and validate the quality of biodiesel produced from this raw material. The studies to optimize the yield and quality of biodiesel were conducted using factorial design. The best combination of factors that presented the highest yield and acidity index within the ANP (National Agency of Petroleum, Natural Gas and Biofuels) specifications was 50%/50% MeOH/EtOH, 1.0% KOH and 1 h of reaction, with a yield of 92.48% and an acidity index of 0.4 mg KOH/g.